2016
DOI: 10.1007/s00221-016-4830-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of unilateral versus bilateral subthalamic nucleus deep brain stimulation on prosaccades and antisaccades in Parkinson’s disease

Abstract: Unilateral deep brain stimulation (DBS) of the subthalamic nucleus (STN) in patients with Parkinson's disease improves skeletomotor function assessed clinically, and bilateral STN DBS improves motor function to a significantly greater extent. It is unknown whether unilateral STN DBS improves oculomotor function and whether bilateral STN DBS improves it to a greater extent. Further, it has also been shown that bilateral, but not unilateral, STN DBS is associated with some impaired cognitive-motor functions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 57 publications
6
46
1
Order By: Relevance
“…Previous attempts at examining the effect of STN DBS on anti-saccade behavior have produced variable observations. Of several studies that specifically addresses effects of STN DBS of anti-saccades [28][29][30] , only one evaluated patients in their off-L-dopa condition, reporting results similar to the present study 30 . Two other studies 28,29 tested patients while they were on their regular dose of L-dopa, and reported no significant effect of STN DBS on anti-saccade performance.…”
Section: Discussionsupporting
confidence: 73%
“…Previous attempts at examining the effect of STN DBS on anti-saccade behavior have produced variable observations. Of several studies that specifically addresses effects of STN DBS of anti-saccades [28][29][30] , only one evaluated patients in their off-L-dopa condition, reporting results similar to the present study 30 . Two other studies 28,29 tested patients while they were on their regular dose of L-dopa, and reported no significant effect of STN DBS on anti-saccade performance.…”
Section: Discussionsupporting
confidence: 73%
“…The dorsolateral prefrontal cortex has been shown to be active during coordinative tasks that involve spatial working memory (Barbey et al 2013; Owen et al 2005), and basal ganglia-prefrontal and basal ganglia-fronto-parietal networks have been shown to be active during the initiation phase of motor sequences (Boecker et al 2008). Interestingly, it has been shown that bilateral, but not unilateral, STN DBS can impair coordinative aspects of movement, for instance performance on a cognitive-motor dual-task (Alberts et al 2008), and response inhibition on the antisaccade task (Goelz et al 2017). Importantly, the cognitive task (n-back) implemented in the Alberts’ study and the antisaccade task implemented in the Goelz’ study both rely heavily upon prefrontal cortical areas (Alberts et al 2008; Goelz et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is admitted that bilateral STN-DBS induces greater therapeutic effect (2). However, bilateral STN-DBS seems also to induce more deleterious side effects, aggravating cognitive processes, verbal fluidity and weight gain in a greater proportion than unilateral stimulation (35,38,39). We previously made the unique description of post-STN-DBS apathy in bilaterally stimulated patients, that was not correlated to dopaminergic reduction (Figure 3)(15-17, 31).…”
Section: Clinical Studymentioning
confidence: 97%
“…Bilateral STN-DBS is applied in patients suffering from advanced stage PD or/with symmetrical symptoms whereas unilateral STN-DBS is advocated for asymmetrical and/or mild stage PD (2). Few clinical studies compared unilateral and bilateral STN-DBS in same patients, but consistently, they highlight that bilateral STN-DBS seems more effective to alleviate motor disturbances such as gait, shaking and oculomotor control (35)(36)(37)41). Thus, it is admitted that bilateral STN-DBS induces greater therapeutic effect (2).…”
Section: Clinical Studymentioning
confidence: 99%
See 1 more Smart Citation